2012
DOI: 10.1021/ja3017297
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Lantibiotic Synthetase That Does Not Require a Leader Peptide on Its Substrate

Abstract: Ribosomally synthesized and post-translationally modified peptides are a rapidly expanding class of natural products. They are typically biosynthesized by modification of a C-terminal segment of the precursor peptide (the core peptide). The precursor peptide also contains an N-terminal leader peptide that is required to guide the biosynthetic enzymes. For bioengineering purposes, the leader peptide is beneficial because it allows promiscuous activity of the biosynthetic enzymes with respect to modification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(138 citation statements)
references
References 47 publications
8
130
0
Order By: Relevance
“…Next, we explored the potential of leader-free macrocyclization following similar approaches used in other RiPP biosynthetic pathways 27,28 . We first attempted in trans cyclization of an ‘inactive’ substrate (MdnA Ac20–49 ) with the MdnA leader peptide MdnA 135 .…”
Section: Resultsmentioning
confidence: 99%
“…Next, we explored the potential of leader-free macrocyclization following similar approaches used in other RiPP biosynthetic pathways 27,28 . We first attempted in trans cyclization of an ‘inactive’ substrate (MdnA Ac20–49 ) with the MdnA leader peptide MdnA 135 .…”
Section: Resultsmentioning
confidence: 99%
“…11,2427 The decrease in processing efficiency can often be rescued in part by the addition of the leader peptide in trans . These studies have demonstrated that, in addition to providing substrate recognition, leader peptides activate their cognate biosynthetic machineries, presumably by biasing the enzymes to an active conformation.…”
Section: Resultsmentioning
confidence: 99%
“…In the LctM ConFusion system, the LctA leader peptide (spanning residues 1–24, violet) was fused to the N -terminus of the LctM enzyme via a (GlySer) 30 linker (red). 32 …”
Section: Figurementioning
confidence: 99%
“…Second, we recently engineered an LctM construct that is genetically fused to the LctA leader peptide in order to make a con stitutively active fusion enzyme (LctM ConFusion ) that catalyzes LctA dehydration without the need for exogenous leader peptide. 32 In addition, the dehydratase and cyclase activities of several LanM enzymes have been successfully split into two polypeptides, 25,3335 an approach that we employ in this study in an attempt to decouple the LctM-catalyzed dehydration and cyclization reactions. Finally, we have recently developed mass spectrometry- and computation-based approaches that enable detailed kinetic and structural characterization of lanthipeptide biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%